72: HIV PREVALENCE AMONG FEMALE SEX WORKERS IN IRAN: A SYSTEMATIC REVIEW. (8th February 2017) - Faramani, Roya Safari; Shahesmaeili, Armita; Hooshyar, Samira Hosseini; Khajehkazemi, Razieh; Nasirian, Maryam; Sharifi, Hamid; Kamali, Kianoosh
Abstract : Background and aims: Although injecting drug use is considered the main route of HIV transmission in Iran, the growing trend of sexual transmission of HIV infection has been much of a concern in recent years. Female sex workers (FSWs) are one of the most important key group populations that have made significant contributions to the spread of HIV in the community. This study was designed to review the current prevalence of HIV infection among this key population in Iran. Methods: The pertinent literature up to July 2014 was retrieved by a systematic search in the 5 electronic databases including PubMed, Scopus, Google Scholar, SID and Iranmedex. The following keywords were searched by using "and" and "or" operators: Sex worker, HIV, Incidence, Prevalence, and Iran. Two independent reviewers evaluated the quality of each paper by a checklist. In case of disagreement between reviewers, a third expert-opinion was sought. EndNote (Version 15) and Microsoft Office Excel 2007 were used respectively to record references and manage the extracted data. Results: Overall, we found 16 studies of which 4 were repetitive and only 2 studies were eligible to be included in the final review. Meta-analysis was not possible due to lack of sufficient studies. One of the two studies was conducted in 14 cities of Iran and the other in Shiraz city. Their sample size were respectively 872 and 278. Based on information retrieved from these two studies, HIV prevalence ranged between 5.4% and 7.4% among FSWs in Iran. Conclusion: FSWs are an important high-risk group in both transmission and acquisition of HIV in the community. Findings of this study also reveal the important role of this group in HIV epidemics in Iran. This requires policy-makers to provide, develop and implement prevention programs for this population. Despite recognition of the importance of this group, only a few studies have been carried out on the incidence and prevalence of HIV infection among FSWs. Hence further studies are needed to be carried out among this group in Iran.